2019
DOI: 10.1111/1541-4337.12491
|View full text |Cite
|
Sign up to set email alerts
|

Global Concerns with B Vitamin Statuses: Biofortification, Fortification, Hidden Hunger, Interactions, and Toxicity

Abstract: The prevalence of undernutrition due to insufficient energy intake has been reduced by nearly 50% since 1990. This reduction is largely attributed to improved yields of staple crops, such as wheat, rice, and maize; however, these improvements did little for micronutrient deficiencies that affect an estimated two billion people worldwide. Starchy staple crops are energy dense but are often lacking in one or more B vitamins, making resource‐constrained people who consume monotonous diets comprised predominantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 140 publications
(172 reference statements)
0
51
0
Order By: Relevance
“…The natural opaque-2 (o2) mutation that is being exploited as a quality protein maize (QPM) leads to the synthesis of increased levels of the essential amino acids lysine and tryptophan ( 94 ). It has also been shown to increase the level of vitamin B3 equivalents due to the availability of more tryptophan and the subsequent conversion to nicotinamide ( 95 ). Furthermore, by combining the o2 and o16 mutants, an increase in lysine and tryptophan of between 40 and 80% has been observed in comparison with the o2 mutant alone ( 96 ).…”
Section: Biofortification Methods To Increase Cereal Vitamin Contentmentioning
confidence: 99%
“…The natural opaque-2 (o2) mutation that is being exploited as a quality protein maize (QPM) leads to the synthesis of increased levels of the essential amino acids lysine and tryptophan ( 94 ). It has also been shown to increase the level of vitamin B3 equivalents due to the availability of more tryptophan and the subsequent conversion to nicotinamide ( 95 ). Furthermore, by combining the o2 and o16 mutants, an increase in lysine and tryptophan of between 40 and 80% has been observed in comparison with the o2 mutant alone ( 96 ).…”
Section: Biofortification Methods To Increase Cereal Vitamin Contentmentioning
confidence: 99%
“…[ 105 ] Additionally, studies have reported that high folate concentration could mask the symptoms of a B 12 deficiency; thus, making it harder to diagnose quickly. [ 106 ] Future studies should look into the effects of a diet high in folate and deficient in B 12 and whether high folate intake could compensate for the lack of B 12 and/or rather mask an existing deficiency.…”
Section: Limiting Factors and Suggestions For Future Researchmentioning
confidence: 99%
“…Humans, however, are not able to synthesize folates de novo and thus are dependent on an adequate external supply with folates [37]. Deficiencies are usually overcome by supplementation or fortification with folic acid [38][39][40][41]. However, in contrast to synthetic supplements, natural folates have not been linked to increased risk of colorectal cancer [29,38,42].…”
Section: Introductionmentioning
confidence: 99%